2004
DOI: 10.3727/000000004773301825
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol, an Extract of Green Tea, Increases Culture Recovery Rates of Isolated Islets from Nonhuman Primate Pancreata and Marginal Grade Human Pancreata

Abstract: Investigations indicate that an extract of green tea, polyphenol, can significantly increase the culture survival rate of rat islets without deteriorating their functionality. In this study, we examined the effect of adding polyphenol to islets isolated from human pancreata and nonhuman primate pancreata. Islets were isolated from human pancreata that did not meet criteria for clinical transplantation (n = 6) and from nonhuman primate pancreata (n = 5). The islets were cultured in CMRL-1066 + 10% FCS with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…The first purpose of the present study, therefore, was to assess whether the addition of EGCG to the islet‐culture medium could reduce any loss of normal islet function caused by damaging events such as apoptosis in normal (conventional) culture conditions. In agreement with previous reports,, this study indicated that EGCG prevented apoptosis and necrotic cell lysis in isolated islets following 48 h in vitro culture. In accord with our result, it has been shown that the exogenous expression of the Bcl‐2 gene or the addition of a caspase inhibitor or leptin — which regulate expression of the Bcl‐2 gene — to culture media, inhibits apoptosis in isolated islets in vitro .…”
Section: Discussionsupporting
confidence: 93%
“…The first purpose of the present study, therefore, was to assess whether the addition of EGCG to the islet‐culture medium could reduce any loss of normal islet function caused by damaging events such as apoptosis in normal (conventional) culture conditions. In agreement with previous reports,, this study indicated that EGCG prevented apoptosis and necrotic cell lysis in isolated islets following 48 h in vitro culture. In accord with our result, it has been shown that the exogenous expression of the Bcl‐2 gene or the addition of a caspase inhibitor or leptin — which regulate expression of the Bcl‐2 gene — to culture media, inhibits apoptosis in isolated islets in vitro .…”
Section: Discussionsupporting
confidence: 93%
“…For example, Zhang et al. [4] reported that only 18% islet mass was recovered after 48‐h culture. Bottino et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many biological functions of PFs have been studied, including anti-inflammatory , antimutagenic (Shiraki et al 1994) and anti-carcinogenic (Huang et al 1992;Yang & Wang 1993) effects. (Hyon 2004;Zhang et al 2004;Ikeguchi et al 2005;Han et al 2005a,b;Hyon et al 2006). Green tea PFs promote the preservation of tissues, such as blood vessels, cornea, nerve, islet cells, articular cartilage and myocardium, at room temperature.…”
Section: Introductionmentioning
confidence: 99%